The protective effect of the spleen in sickle cell patients. A comparative study between patients with asplenia/hyposplenism and hypersplenism - Peretz, Sari; Livshits, Leonid; Pretorius, Etheresia; Makhro, Asya; Bogdanova, Anna; Gassmann, Max; Koren, Ariel; Levin, Carina (Frontiers in Physiology, 2022)
Sickle cell disease (SCD) is caused by a point mutation in the beta-globin gene. SCD is characterized by chronic hemolytic anemia, vaso-occlusive events leading to tissue ischemia, and progressive organ failure. Chronic inflammatory state is part of the pathophysiology of SCD. Patients with SCD have extremely variable phenotypes, from mild disease to severe complications including early age death. The spleen is commonly injured in SCD. Early splenic dysfunction and progressive spleen atrophy are common. Splenomegaly and hypersplenism can also occur with the loss of the crucial splenic function. Acute, life-threatening spleen-related complications in SCD are well studied. The association of laboratory parameters with the spleen status including hyposplenism, asplenia, and splenomegaly/hypersplenism, and their implication in vaso-occlusive crisis and long-term complications in SCD remain to be determined. We evaluated the association between the spleen status with clinical and laboratory parameters in 31 SCD patients: Group a) Patients with asplenia/hyposplenism (N=22) (including auto-splenectomy and splenectomized patients) vs. Group b) patients with splenomegaly and or hypersplenism (N=9). Laboratory studies included: Complete Blood Count, reticulocyte count, iron metabolism parameters, C Reactive Protein (CRP), Hb variant distribution, and D-dimer. Metabolic and morphological red blood cell (RBC) studies included: density gradient (by Percoll), glucose consumption, lactate release, and K+ leakage, fetal RBC (F-Cells) and F-Reticulocytes, annexinV+, CD71+, oxidative stress measured by GSH presence in RBC and finally Howell Jolly Bodies count were all analyzed by Flow Cytometry. Scanning electron microscopy analysis of RBC was also performed. Patients with asplenia/hyposplenism showed significantly higher WBC, platelet, Hematocrit, hemoglobin S, CRP, D-dimer, Gamma Glutamyl Transferase (GGT), cholesterol, transferrin, annexin V+ RBCs, CD71+ RBCs, together with a markedly lower F Reticulocyte levels in comparison with splenomegaly/hypersplenism patients. In summary, important differences were also found between the groups in the studied RBCs parameters. Further studies are required to elucidate the effect of the spleen including hyper and hypo-splenia on laboratory parameters and in clinical manifestations, vascular pathology, and long-term complications of SCD. The benefits and risks of splenectomy compared to chronic transfusion need to be evaluated in clinical trials and the standard approach managing hypersplenism in SCD patients should be re-evaluated.